Analisis Pembelajaran Matematika dengan Mengimplementasikan Kurikulum Merdeka di SMP Negeri 8 Medan - Rini Sri Susilawati Simbolon; Seri Haryati Harahap; Ratna Soraya; Rosliana Siregar (Journal on Education, 2024)
This research aims to: Understand the mathematics learning process by implementing the independent curriculum at SMP Negeri 8 Medan. This research method uses qualitative research which emphasizes analysis or descriptiveness. The subjects in this research were mathematics teachers who had become driving teachers and students of class VII SMP Negeri 8 Medan. The data collection techniques used were observation, interviews and documentation. The results of the research show that learning mathematics by implementing the independent curriculum at SMP Negeri 8 Medan has had an impact on changes in students' behavior in learning, as can be seen from the results of observations that students are more active in learning activities and creative in their work. assignments so that student learning outcomes match the learning objectives. Meanwhile, learning mathematics by implementing the independent curriculum by teachers can respond to learning needs by paying attention to the preparation, implementation and assessment of mathematics learning. This research shows that learning mathematics by implementing the independent curriculum has an impact on good changes in students' behavior and learning outcomes and the implementation of learning must be appropriate. with independent curriculum learning steps.